A tryparedoxin-coupled biosensor reveals a mitochondrial trypanothione metabolism in trypanosomes - Ebersoll, Samantha; Bogacz, Marta; Günter, Lina M; Dick, Tobias P.; Krauth-Siegel, Renate (eLife, 2020)
Trypanosomes have a trypanothione redox metabolism that provides the reducing equivalents for numerous essential processes, most being mediated by tryparedoxin (Tpx). While the biosynthesis and reduction of trypanothione are cytosolic, the molecular basis of the thiol redox homeostasis in the single mitochondrion of these parasites has remained largely unknown. Here we expressed Tpx-roGFP2, roGFP2-hGrx1 or roGFP2 in either the cytosol or mitochondrion of Trypanosoma brucei. We show that the novel Tpx-roGFP2 is a superior probe for the trypanothione redox couple and that the mitochondrial matrix harbors a trypanothione system. Inhibition of trypanothione biosynthesis by the anti-trypanosomal drug Eflornithine impairs the ability of the cytosol and mitochondrion to cope with exogenous oxidative stresses, indicating a direct link between both thiol systems. Tpx depletion abolishes the cytosolic, but only partially affects the mitochondrial sensor response to H2O2. This strongly suggests that the mitochondrion harbors some Tpx and, another, as yet unidentified, oxidoreductase.